2023
DOI: 10.1242/jeb.244984
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent metabolic consequences of food deprivation in the European sardine

Abstract: Aquatic ecosystems can exhibit seasonal variation in resource availability and animals have evolved to cope with the associated caloric restriction. During winter in the NW Mediterranean Sea, the European sardine Sardina pilchardus naturally experiences caloric restriction due to a decrease in diversity and quantity of plankton. Ongoing global warming has, however, had deleterious effects on plankton communities such that food shortages may occur throughout the year, especially under warm conditions in the sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In combination with the processes we identified as helping reduce Ṁ O 2 standard , other studies have shown that increased mitochondrial efficiency (i.e. less proton leak) or reductions in mitochondrial abundance ( Guderley and St-Pierre, 2002 ; Salin et al, 2018 ; Secor and Carey, 2016 ; Thoral et al, 2023 ) can contribute greatly to reductions in Ṁ O 2 standard when food is limited.…”
Section: Discussionmentioning
confidence: 69%
“…In combination with the processes we identified as helping reduce Ṁ O 2 standard , other studies have shown that increased mitochondrial efficiency (i.e. less proton leak) or reductions in mitochondrial abundance ( Guderley and St-Pierre, 2002 ; Salin et al, 2018 ; Secor and Carey, 2016 ; Thoral et al, 2023 ) can contribute greatly to reductions in Ṁ O 2 standard when food is limited.…”
Section: Discussionmentioning
confidence: 69%
“…(a) Parental condition and offspring temperature increased selection on offspring metabolism availability often selects for reduced metabolic rates [75], presumably to conserve energy reserves. Further, temperature and food availability can interact to affect metabolism in complex ways, with evidence for temperature mediating both an increase and decrease in metabolism with increases in food availability [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…[24,[38][39][40][41][42]44,93,94]) life-history stage (e.g. [20,32,40,[47][48][49][50]66,91,123,126,[129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147]) interactive effects of intrinsic factors ecological life style pelagic versus benthic (e.g. [20,24,34,40,92,93]) food habits (e.g.…”
Section: Interactive Effects Of Intrinsic Factorsmentioning
confidence: 99%
“…Higher temperature speeds up metabolism, whereas higher salinity reduces osmoregulatory metabolic demand in marine organisms. However, hypersaline conditions may increase metabolic costs in freshwater/estuarine organisms [120][121][122][123] temperature and pH (CO 2 ) variable (species-specific) combined effects of temperature and acidification (CO 2 levels) vary with species for unknown reasons [124,125] ( [84,121,126,127] temperature and food supply complex thermal sensitivity of metabolism varies with food supply in complex ways [128,129] temperature and toxicants complex thermal sensitivity of metabolic rate in a moth depended on an insecticide treatment when acclimated at 22°C, but not when acclimated at 28°C [130] temperature and microplastics complex in an aquatic amphipod, temperature effects are positive at low microplastic concentration, but negative at high microplastic concentration, for unknown reasons [131] temperature and latitude positive (low to high latitude) high-latitude populations in relatively cool habitats tend to show more thermal sensitivity of metabolic rate than that of low latitude populations in warmer habitats [132][133][134][135] temperature and altitude positive (low to high altitude) a high-altitude population of the tsetse fly Glossina pallidipes in a cool habitat showed higher temperature sensitivity of metabolic rate than did lowaltitude populations in warmer habitats [136] temperature and ecological life style complex invasive crayfish show higher metabolic rates at warm temperatures, but lower metabolic rates at cooler temperatures than do native crayfish [137] light and predator cues positive or negative metabolic rate of an aquatic amphipod changes in response to fish predator cues in light, but not in dark [138] interactive effects of intrinsic and extrinsic factors type direction of interactive effect a underlying mechanism selected sources body size and ecological life style pelagic versus benthic positive or negative (comparing pelagic species to benthic species) pelagic invertebrate/protist species (or life-stages) tend to show steeper metabolic scaling than do related benthic species (or life-stages), possibly because of age-and size-specific differences in locomotor costs, cellular mode of growth, or predation-caused rates of mortality, growth and reproduction. Opposite patterns are shown for teleost fishes, possibly owing, at least in part, to their lesser vulnerability to predation (associated with their larger body size and more rapid escape movements), and to thei...…”
Section: Interactive Effects Of Intrinsic Factorsmentioning
confidence: 99%
See 1 more Smart Citation